Effect of curcumin on aging retinal pigment epithelial cells - Zhu W; Wu Y; Meng YF; Wang JY; Xu M; Tao JJ; Lu J (Dove Medical Press, 2015)
Wei Zhu,1,* Yan Wu,2,* Yi-Fang Meng,1 Jin-Yu Wang,1 Ming Xu,1 Jian-Jun Tao,1 Jiong Lu1 1Department of Ophthalmology, Changshu No 2 People’s Hospital, Changshu, 2Department of Ophthalmology, The First People’s Hospital of Kunshan Affiliated with Jiangsu University, Suzhou, People’s Republic of China *These authors contributed equally to this work Abstract: Age-related macular degeneration (AMD) is now one of the leading causes of blindness in the elderly population. The antioxidative effects of curcumin on aging retinal pigment epithelial (RPE) cells are still unclear. We conducted an in vitro study to investigate the effects of curcumin on aging RPE cells. A pulsed H2O2 exposure aging model was adopted. Aging RPE cells were treated with curcumin 20 µM, 40 µM, and 80 µM. Apoptosis of RPE cells was analyzed by flow cytometry. The intracellular reactive oxygen species concentration was detected using a specific probe and apoptosis-associated proteins were detected by Western blot. Expression of oxidative biomarkers, including superoxide dismutase, maleic dialdehyde, and glutathione, was detected commercially available assay kits. Compared with normal cells, lower cell viability, higher apoptosis rates, and more severe oxidation status were identified in the aging RPE cell model. Curcumin improved cell viability and decreased apoptosis and oxidative stress. Further, curcumin had a significant influence on expression of apoptosis-associated proteins and oxidative stress biomarkers. In conclusion, treatment with curcumin was able to regulate proliferation, oxidative stress, and apoptosis in aging RPE cells. Accordingly, application of curcumin may be a novel strategy to protect against age-related change in AMD. Keywords: curcumin, retinal pigment epithelium, apoptosis, age-related macular degeneration